The initial record of phytoplankton in Hon Lao islet of Cu Lao Cham World Biosphere Reserve, Quang Nam Province - Le, Thi Trang; Phan, Doan Dang; Phan, Cong Sanh; Nguyen, Thanh Huy; Tran, Thi Phuong Thao; Nguyen, Van Tu (Vietnam Journal of Marine Science and Technology, 2025)
The study was conducted to assess the phytoplankton biodiversity in Hon Lao Islet. The investigated sites included streams and lakes located on the islet. We identified 126 phytoplankton species, belonging to 62 genera, 43 families, 27 orders, 11 classes, and 6 divisions, including Cyanobacteria, Ochrophyta, Bacillariophyta, Chlorophyta, Euglenophyta, and Dinophyta. Among these groups, Chlorophyta and Bacillariophyta were the most dominant in terms of species. The average cell density on Hon Lao islet was 11,347 ± 4,149 cells/liter (mean ± SE) in the dry season and 3,355 ± 2,601 cells/liter in the rainy season, respectively. The dominant species that contributed to the studied area were different in both seasons, such as Oscillatoria princeps, O. limosa, Lyngbya martensiana, Anabaena inaequalis, Botryococcus braunii, Ulnaria ulna, Gomphonema parvulum, Fragilaria sp., Iconella tenera, and Phacus orbicularis from the dry season, and species of Oscillatoria sp., Spirogyra ionia, Radiococcus polycoccus, Fragilaria sp., Eunotia pectinalis, E. minor, and Navicula cryptocephala from the rainy season. Analysis of the Bray-Curtis similarity index showed that phytoplankton composition differed between monitoring sites.